Improving existing prsg using qsp - Markovski, Jasen; Dimitrova, Vesna (My University, 2003)
Pseudo random sequence generators (PRSG) are deterministic algorithms that produce sequences of elements that imitate natural random behavior. Random sequences have extensive use in scientific experiments as input sequences for different kinds of simulators, in cryptography for preparation of keys and establishing communication, in authentication for preparation of identification numbers, smart cards, serial numbers, etc. For this reason the field of pseudo random generators is widely exploited. However, widely available PRSGs have limited periods (for example, 264), which mean that the pseudo random sequences start repeating the same elements (after at most 264 elements). This makes them inappropriate for large-scale scientific experiments, cryptography and authentication, because they produce predictable pseudo random output sequences. In this paper we will try to improve some of existing linear PRSGs using quasigroup sequence processing (QSP).
Keywords: pseudo random sequence generator, quasigroup sequence processing, period of PRSG